2015
DOI: 10.1039/c5ra05227k
|View full text |Cite
|
Sign up to set email alerts
|

Ternary composites of linear and hyperbranched polyimides with nanoscale silica for low dielectric constant, high transparency, and high thermal stability

Abstract: A new series of ternary polyimide-silica composites was developed to obtain polymer films with low dielectric constant, high optical transparency, and good thermal stability. By using a linear polyamic acid with triethoxysilane termini and a hyperbranched polyimide with peripheral hydroxyl groups (HBPI BPADA-TAP(OH) ), the ternary composites were fabricated through in situ imidization and sol-gel reaction with tetraethoxysilane. The results show that the composite films exhibit significantly improved propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Second, the fracture interface of the PI/Gh-BN film was observed to be densely branched, enabling the film to prevent crack propagation via energy absorption. 46 Fig. 2(g) and (h) show the fracture cross-sections of the PI/EPPOSS film.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the fracture interface of the PI/Gh-BN film was observed to be densely branched, enabling the film to prevent crack propagation via energy absorption. 46 Fig. 2(g) and (h) show the fracture cross-sections of the PI/EPPOSS film.…”
Section: Resultsmentioning
confidence: 99%
“…TEOS is a standard sol-gel precursor of SiO 2 , and APTES is a standard network-modier that has been used to (i) introduce amino-functionalities in SiO 2 , 20 and (ii) as a compatibilizer between SiO 2 and PIs in the preparation of PI/SiO 2 hybrids. 21,22 Note that other approaches to covalently link PIs to SiO 2 include (i) employing epoxy-functionalized silicon alkoxides, 23 (ii) the use of PI monomers with pendant OH groups able to co-condense with TEOS, 24 (iii) employing pre-formed PMMA-functionalized SiO 2 particles, where the PMMA-functionalization allows for crosslinking with the PI via transesterication, 25 (iv) to decorate PIs with pendant silane side-groups that are able to co-condense with TEOS, 26 or to employ APTES end-capped poly(amic acid) species. 27 However, all the PI/SiO 2 hybrids and composites reported to date have been prepared employing classical, non-green routes, i.e.…”
Section: Hydrothermal Synthesis Of Pi6/sio 2 Hybrid Materialsmentioning
confidence: 99%
“…by polycondensation in toxic solvents such as DMF or NMP via poly(amic acid) intermediates. [21][22][23][24][25][26][27] From our studies of HTP of PI6, we restricted the employed reaction parameters to T R ¼ 200 C, t R ¼ 24 h and the autogenous pH ¼ 4, generated by the acidity of PMA. We investigated three types of precursor mixtures: (i) HMDA/PMA/TEOS (experiments #1-3) (ii) HMDA/PMA/TEOS/APTES (experiments #4-6), and (iii) HMDA/PMA/APTES (experiments #7-9), all summarized in Table 1.…”
Section: Hydrothermal Synthesis Of Pi6/sio 2 Hybrid Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,[26][27][28][29] We have recently fabricated a novel ternary hybrid system: a hydroxyl terminated hyperbranched polyimide with linear PI/SiO 2 (ref. [30][31][32] that has excellent properties, for example, a very low dielectric constant, reduced organic particle size [30][31][32][33] and good thermal stability. Additionally, we have reported that by using a exible organosilane agent nano-sized domains of SiO 2 are formed and that this produces a highly dispersed material.…”
Section: Introductionmentioning
confidence: 99%